2022
DOI: 10.32528/ellite.v7i2.8354
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Artificial Intelligent Technology Used (Duolingo Application) To Enhance English Learning

Abstract: This research aims to figure out the effect of Artificial Intelligence Technology in Duolingo Application to Enhance Speaking and Listening Ability. This study uses a quantitative technique where the researcher conducts experimental research using a quasi-experimental design. This research was completed at Hamzanwadi University with the subjects of this study were all students of second semester with class C English program with a total of 31 students. Where 16 students were the experimental class and 15 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Duolingo was introduced as a versatile resource for learning different skills both within the classroom and beyond, available for students to access at any point. This flexibility led to an increase in students' enjoyment and success in practicing listening and speaking skills, in line with findings by Handini et al (2022). Over the course of six sessions, there was a noticeable shift in students' attitudes towards English learning; they became more engaged and less prone to distractions, attributing to the focused and personalized learning experience facilitated by Duolingo.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Duolingo was introduced as a versatile resource for learning different skills both within the classroom and beyond, available for students to access at any point. This flexibility led to an increase in students' enjoyment and success in practicing listening and speaking skills, in line with findings by Handini et al (2022). Over the course of six sessions, there was a noticeable shift in students' attitudes towards English learning; they became more engaged and less prone to distractions, attributing to the focused and personalized learning experience facilitated by Duolingo.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, Quizizz was employed both as a teaching medium and an assessment tool in relation to the specified topics. Similarly, a prior study by Handini et al (2022) on Duolingo demonstrated that students effectively utilized the app as a learning medium, answering questions confidently and fully exploiting the opportunities to enhance their English skills. Furthermore, research by Polakova & Klimova (2023) highlighted the benefits of using natural machine translation (NMT) technology, specifically DeepL, in learning foreign languages.…”
Section: Introductionmentioning
confidence: 87%